DESAIN PEMBELAJARAN UNTUK TRANSFORMASI SOSIAL (Studi Perbandingan Pemikiran Paulo Freire dan Ivan Illich tentang Pendidikan Pembebasan) - Muh. Hanif (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2014)
Paulo Freire and Ivan Illich are prominent figures in contemporary education, who broke the stable system of education. Paulo Freire suggests to stop bank style education and to promote andragogy education, which views both teacher and students equally. Education should be actualized through facing problems and should be able to omit naÃ¯ve and magic awareness replaced with critical and transformative awareness. Different from Freire, Illich offers to free the society from formal schools. Education should be run in an open learning network. Technical skills can be taught by drilling. In addition, social transformation will happen only if there are epimethean people that are minority in existence.